The Emergence of Creative Leaders Within Social Networks: The Case of Andy Warhol in the Art World of New York - Samdanis, Marios; Lee, Soo Hee (Frontiers in Psychology, 2021)
The creative leadership literature has identified personality traits, skills, states and behaviours which are effective within creative contexts and organisations, but it is yet to address how creative leaders emerge from social networks. This conceptual paper delineates the processes of creative leader emergence within the context of contemporary visual arts. Using a relational view of creative-leader emergence, this paper incorporates the leader-emergence processes of achievement and ascription, and then adjusts them to the context of the art world. We argue that both competence and identity contribute to the status construction of creative leaders, by enabling their emergence within social networks. In addition to the processes of leader prototypicality through which leaders emerge within groups, we also identify processes of leader atypicality through which creative leaders emerge within network structures. Finally, our conceptual analysis is illustrated by the case of Pop artist Andy Warhol, focusing on his emergence as a creative leader within the art world of New York and his art studio, the Factory.